قيم التضامن والتكافل في الأدب الجزائري - عزّ الدِّين, جلاوجي (roa; Vol 2 (2021): مجلة رؤى في الآداب والعلوم الإنسانية, 2021)
يتتبع هذا المقال حضور قيم التضامن والتكافل في الأدب الجزائري، شعرا ونثرا، مع الوطن/ الذات "الجزائر" ومع الذوات الكبيرة والكبرى فالأكبر، المغرب العربي، الوطن العربي وفلسطين بالخصوص، ومع الإنسانية جمعاء.   كلمات مفتاحية : قيم التضامن، الأدب الجزائري، الشعر الجزائري، فلسطين، المغرب العربي، الوطن العربي، الإنسانية. Summary: This article follows the present of solidarity values and the collaboration in the Algerian literature: poetry and prose with the self nation " Algeria" and with the big selves, great to the greatest ones: the Arab Maghreb, the Arab world, particularly Palestine and with all humanity. Key words : solidarity values, the Algerian literature, the Algeria poetry, Palestine, the Arab Magheb, the Arab world, humanity